The Global Boom of the Infrastructure’s Implementation Regarding the Achievement of the Photovoltaic Energy - Gabriela Opait (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
The power of the electrical energy which was achieved by a single photovoltaic cell it measures between 1 or 2 watts and the architecture of the systems which reflect the chains of photovoltaic cells has the designation of panel. At the global level, the first three countries which head in the achievement of the solar photovoltaic energy are China, the United States and Japan.